Organizational Commitment of Lecturers in Improving The Quality of Education - Hotni Sari Harahap; Amiruddin Siahaan; Rahmah Fithriani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2026)
This study aims to fill this gap by exploring how lecturers’ organizational commitment in its three main dimensions can contribute to improving the quality of education at Alwashliyah University Medan. This study employs a qualitative approach, with data collection conducted through surveys, in-depth interviews, and institutional document analysis involving 85 lecturers. The data obtained were analyzed using NVivo and were systematically collected until data saturation was achieved. Data validity was examined through several techniques, namely credibility, transferability, dependability, confirmability, and triangulation. The conclusions of this study reveal that lecturers’ organizational commitment at Alwashliyah University Medan demonstrates emotional, moral, and rational attachment that forms the basis of loyalty to the institution. Normative commitment appears to be the most dominant, driven by moral awareness, religious values, and ethical responsibility inherent in an Islamic-based organizational culture. Efforts to enhance lecturers’ organizational commitment are carried out through managerial strategies of university leadership and individual initiatives of the lecturers. On the other hand, lecturers strengthen their commitment through improving professionalism, collaborative research, adaptation to technology, and the establishment of solid academic networks.